Weaving a Web of ideas. - Cherry, S.M (IEEE spectrum)
Engines that search for meaning rather than words will make the Web more manageable. Committees of researchers from around the globe want to make the Web more homogeneous, more data-like, more amenable to computer understanding-and then agents won't have to be so bright. In other words, if Web pages could contain their own semantics-if we had a Semantic Web-software agents wouldn't need to know the meanings behind the words.